A novel method for measuring viscoelastic parameters of epoxy resins under water bath environments using embedded strain gauges. (January 2023) - Shi, Xinghua; Qiu, Yuanying; Jia, Fei; Ma, Hongbo
Abstract: Epoxy resins are a class of viscoelastic hygroscopic polymers widely used in plastic packaged devices. Stress relaxation and yielding may occur in plastic packaged devices under thermal-hygro environments, which seriously affect the reliability of the devices. It is important to obtain accurate viscoelastic parameters of the hygroscopic materials for analyzing the stresses and strains of plastic packaged devices. In this paper, a novel method for measuring the viscoelastic parameters of epoxy resins under water bath environments by using embedded strain gauges is proposed. A kind of epoxy resin-copper bi-layer plate is fabricated, and the biaxial strain gauges are embedded between the epoxy resin layer and the copper layer to monitor the deformations. The interfacial strains of the two test pieces at 85 °C/100% relative humidity are continuously measured up to 144 h. Combine the experimental strain curves and the analytical representation, the viscoelastic parameters of the epoxy resins are obtained by curve fitting with MATLAB and genetic algorithm. It is found that the viscoelasticity of epoxy resins could be described by an exponential function of order five shear modulus and relaxation times, and the interfacial strain curves obtained by genetic algorithm fit well with the experimental ones. The proposed testing and solving methods provide a valuable reference for getting the time-dependent viscoelasticities of epoxy resins under thermal-hygro environments. Highlights: The analytical representations on the hygro-mechanical behavior of the elastic-viscoelastic bi-layer plate are deduced. The interfacial hygro-mechanical strains of the epoxy resin-copper bi-layer plates are measured exploratory in water. The viscoelasticities of the epoxy resins are solved by fitting the strain curves with MATLAB based on the genetic algorithm. The method provides a novel means to analyze the viscoelasticity of hygroscopic materials under water bath environments.